2011
DOI: 10.1111/j.1742-4658.2010.07994.x
|View full text |Cite
|
Sign up to set email alerts
|

The subcellular organization of strictosidine biosynthesis in Catharanthus roseus epidermis highlights several trans‐tonoplast translocations of intermediate metabolites

Abstract: Catharanthus roseus synthesizes a wide range of valuable monoterpene indole alkaloids, some of which have recently been recognized as functioning in plant defence mechanisms. More specifically, in aerial organ epidermal cells, vacuole-accumulated strictosidine displays a dual fate, being either the precursor of all monoterpene indole alkaloids after export from the vacuole, or the substrate for a defence mechanism based on the massive protein cross-linking, which occurs subsequent to organelle membrane disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 49 publications
7
51
0
Order By: Relevance
“…RT-PCR analysis of leaf epidermis enriched transcripts showed that the levels of UGT6 and UGT8 were at least 10-fold lower than those found in whole leaves, while UGT7 transcripts were more equally distributed ( Figure 4A). By contrast, transcripts for LAMT and SLS, well known to be preferentially expressed in the leaf epidermis Guirimand et al, 2011), were two-to fourfold more enriched in these cells. Together, these results suggested that both UGT-6 and -8 are preferentially expressed within periwinkle leaves rather than in leaf epidermal cells, where the last two steps in secologanin assembly are expressed.…”
Section: Preferential Expression Of Ugts In Plant Organs and Leaf Cellsmentioning
confidence: 76%
See 1 more Smart Citation
“…RT-PCR analysis of leaf epidermis enriched transcripts showed that the levels of UGT6 and UGT8 were at least 10-fold lower than those found in whole leaves, while UGT7 transcripts were more equally distributed ( Figure 4A). By contrast, transcripts for LAMT and SLS, well known to be preferentially expressed in the leaf epidermis Guirimand et al, 2011), were two-to fourfold more enriched in these cells. Together, these results suggested that both UGT-6 and -8 are preferentially expressed within periwinkle leaves rather than in leaf epidermal cells, where the last two steps in secologanin assembly are expressed.…”
Section: Preferential Expression Of Ugts In Plant Organs and Leaf Cellsmentioning
confidence: 76%
“…However, the preference of native and recombinant loganic acid O-methyltransferase (LAMT) from periwinkle for loganic acid (5, Figure 1G) but not 7-deoxyloganic acid (4, Figure 1I) makes the alternative pathway less likely in periwinkle plants. The last two steps to form secologanin involve LAMT and secologanin synthase (SLS) ( Figure 1H), which are preferentially expressed in the leaf epidermis of periwinkle plants, as determined by carborundum abrasion extraction and in situ hybridization methods (Guirimand et al, 2011). The formation of secologanin in the leaf epidermis suggests that an undefined iridoid, possibly loganic acid or some earlier intermediate, must be transported to the leaf epidermis for its elaboration, and this cell type is also the site of expression of enzymes such as Trp decarboxylase and strictosidine synthase, which are required to elaborate the formation of strictosidine from which all of the MIAs of periwinkle are derived (Facchini and De Luca, 2008;Guirimand et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most plant P450s characterized to date function as endoplasmic reticulum (ER)-anchored enzymes, as exemplified in C. roseus for CYP71D12, CYP72A1, and CYP76B6 (Guirimand et al, 2009(Guirimand et al, , 2011a(Guirimand et al, , 2011b. However, the recent localization of two carotenoid-hydroxylating P450s to plastids (Quinlan et al, 2012) prompted us to analyze the subcellular localization of CYP71D351 (T16H2).…”
Section: Cyp71d351 (T16h2) Is An Endoplasmic Reticulum-anchored Enzymementioning
confidence: 99%
“…Recently, glucosidal intermediates for alkaloid biosynthesis have also been suggested to serve as a defense system (Nomura et al, 2008;Guirimand et al, 2010Guirimand et al, , 2011. In these systems, toxic aglycons are released from inactive glucosides by corresponding b-glucosidases and myrosinases existing in distinct subcellular compartments.…”
Section: Physiological Role Of Tgtce-mediated Tulipalin Formationmentioning
confidence: 99%